Metaphor and Abstraction in the Experience of Artist Juan Miro (An Analytical Study) - Ritaj Ibrahim Badn (Kurdish Studies, 2023)
This research, entitled "Metaphor and Abstraction in the Work of Joan Miró (Analytical Study)", is based on the importance of the research topic, through providing formulations for new or innovative aspects in the worlds of innovation and creativity of the most important contemporary artistic productions and breaking out the boundaries of the ordinary.The first chapter (General Framework) consists of the research problem and its importance, represented by several problem questions:What are the metaphors that artist Joan Miró used in his artistic experience after reformulating it with abstract, surrealist structures that are reduced in formation and its intellectual presentation of meaning?What are the symbolic meanings that distinguish his artistic productions from the other?What are the mechanisms followed by him in the artistic achievement?To what extent is it possible to emerge from the experience of artist Joan Miró, with innovative results that can be benefited from in the world of art and reality through the exploration of ways of innovation, experimentation, and exploration?The aim of the research is to identify the most important multiple metaphors that the artist acquired from the world of reality, starting with the artistic elements and diverse vocabulary between the consumer and the manufacturer, with the research being defined by its thematic, spatial, and temporal limits included in the metaphor and abstraction in the experience of artist Joan Miró and defining his artistic terms, (metaphor and abstraction) worked on.Through the second chapter (Theoretical Framework), which includes two topics:The first topic: Metaphor and abstraction and its implications in modern painting.The second topic: Metaphor and abstraction and its implications in the experience of artist Joan Miró, with a detailed analysis of the forms of the research samples, including the theoretical framework in its two topics, and the results and conclusions.